Registration of 'Merem' Spring Malting Barley. Issue 3 (18th July 2014) - Hu, G.; Obert, D. E.; Evans, C. P.; Satterfield, K.; Ellberg, S.; Marshall, J. M.; Budde, A.; Martens, C.
Abstract : Improvement of malting barley ( Hordeum vulgare L.) cultivars is important for both the malting industry and barley production. A new, two‐row spring, malting barley cultivar named 'Merem' (Reg. No. CV‐353, PI 668574), was developed by bulked selection approach at the USDA–ARS, Aberdeen, ID, in cooperation with the University of Idaho Agricultural Experiment Station. Merem was tested at the USDA–ARS and all other cooperative trials as 02Ab17271. 02Ab17271 is a selection from the cross 85Ab2323/'Merit'. 85Ab2323, a USDA–ARS experimental selection from the cross '79Ab10542/78Ab6871', is a high‐yielding, well‐adapted, two‐row spring barley from the USDA–ARS Aberdeen, ID. Both 79Ab10542 and 78Ab6871 are experimental selections from the USDA–ARS, Aberdeen, ID. Merit was developed by Busch Agricultural Resources LLC., at Fort Collins, CO, and was selected from the cross 'Manley/2B80‐350'. Merem has higher yield than 'Harrington' and 'AC Metcalfe' in irrigated conditions and higher malt extract than all control lines of Harrington, AC Metcalfe, and 'Conrad'. Merem provides another option for the malting barley industry among two‐row, malting barley cultivars.